2018
DOI: 10.1159/000488964
|View full text |Cite
|
Sign up to set email alerts
|

Previous Exercise Effects in Cisplatin-Induced Renal Lesions in Rats

Abstract: Background/Aims: Physical training has beneficial effects on endothelial function and can influence the regeneration of the endothelial cell. We investigated the effect of physical training on cisplatin (CP)-induced acute kidney injury and assessed the impact of training on endothelial structure and function, and on the inflammatory processes in rats. Methods: We injected male Wistar rats subjected to previous physical training in treadmill running (trained, TR) or not (sedentary, SED) with CP (5 mg/kg) (TR+CP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…Furthermore, in both instances the effect of exercise was shown in pre-dialysis CKD patients with no studies demonstrating the effects of exercise in the AKI setting. Despite this, the findings are consistent with other work in animal models [23][24][25][26][27][28][29] which have demonstrated an improvement in renal function following exercise in the AKI setting. Although the precise mechanism by which exercise, or increased levels of physical activity may protect against or even promote recovery following AKI in humans remains unclear, one mechanism which may be crucial is the well-reported anti-inflammatory effect of exercise.…”
Section: Exercise and Akisupporting
confidence: 91%
“…Furthermore, in both instances the effect of exercise was shown in pre-dialysis CKD patients with no studies demonstrating the effects of exercise in the AKI setting. Despite this, the findings are consistent with other work in animal models [23][24][25][26][27][28][29] which have demonstrated an improvement in renal function following exercise in the AKI setting. Although the precise mechanism by which exercise, or increased levels of physical activity may protect against or even promote recovery following AKI in humans remains unclear, one mechanism which may be crucial is the well-reported anti-inflammatory effect of exercise.…”
Section: Exercise and Akisupporting
confidence: 91%
“…15 The number of JG12-positive cells in each cortical interstitial 30-grid field was determined in the renal cortex, and the mean counts were calculated for each section. 16 It has been demonstrated that the semi-quantitative scoring system is not only reproducible among different observers but that data are also highly correlated with those obtained through computerized morphometry by several authors. 17…”
Section: Immunohistochemical Studiesmentioning
confidence: 88%
“…To quantify JG12, synaptopodin and cubilin staining, each glomerulus or cortical field (measuring 0.100 mm 2 each) was semi-quantitatively graded, and the mean score per section was calculated. 16 The scores mainly reflected changes in the extent rather than in the intensity of staining and were dependent on the percentage of the glomeruli or grid field, showing positive staining. The scores were determined as follows: 0 = absent or < 5% staining; 1 = 5-25%; 2 = 25-50%; 3 = 50-75% and 4 > 75% staining.…”
Section: Immunohistochemical Studiesmentioning
confidence: 99%
“…(36). In vitro and in vivo studies have shown that increased eNOS activity resulted in endothelial cell proliferation and migration, and increased angiogenesis (37,38). Increased NO production in the LOS + Calcitriol group compared to that in the LOS group have resulted in decreased vasoconstriction induced by reduced AT 1 receptor activity in renal tissue from these animals.…”
Section: Discussionmentioning
confidence: 99%